Vibration of Multi-Chamber Shell Structures with Discontinuously Variable Cross-Sections - Drewko, J.; Sperski, M. (Engineering Transactions, 1991)
The paper presents the general integral of a set of differentia! equations describing vibrations of a multichamber prismatic shell made of a linear-elastic orthotropic material. The solution is used to construct the equations of forced vibrations of a structure consisting of a series of interconnected shells of various cross-sections. Displacement amplitudes of such shell structures subject to stationary vibrations have been found, together with the resonance frequencies and the principal vibration modes.